STUDI ANALISIS HUKUM ANALISIS HUKUM PERKAWINAN DI BAWAH UMUR MENURUT UNDANG-UNDANG PERKAWINAN NO. 1 TAHUN 1974 DAN IMAM SYAFI’I - ., Bukhori; Hambali, Yoyo (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2016)
The problem of this research is how the law of underage marriage according to Law No. 1 of 1974 and according to Imam Shafi'i, and whether the similarities anddifferences underage marriage law by Act No. 1 of 1974 and Imam Shafi'i ? This is a qualitative research method research library. Through the study concluded that based on the Marriage Law No. 1 of 1974 is the minimum age to be allowed to mate, the male 19 and female 16 years of article 7, paragraph 2, while according to the Shafi'i that age permissibility perform a marriage is determined by the maturity of someone in this is the age of majority to carry out the marriage is 15 years old. Similarities between the two, they both require the existence in a marriage. Both were very clear in explaining that the trustee is entitled to be a father/grandfather and asked permission to one of the two.